Anchored linear oligonucleotides: the effective tool for the real-time measurement of uracil DNA glycosylase activity - Ligasová, Anna; Rosenberg, Ivan; Bocková, Markéta; Homola, Jiří; Koberna, Karel (Open biology, 2021)
Base excision repair is one of the important DNA repair mechanisms in cells. The fundamental role in this complex process is played by DNA glycosylases. Here, we present a novel approach for the real-time measurement of uracil DNA glycosylase activity, which employs selected oligonucleotides immobilized on the surface of magnetic nanoparticles and Förster resonance energy transfer. We also show that the approach can be performed by surface plasmon resonance sensor technology. We demonstrate that the immobilization of oligonucleotides provides much more reliable data than the free oligonucleotides including molecular beacons. Moreover, our results show that the method provides the possibility to address the relationship between the efficiency of uracil DNA glycosylase activity and the arrangement of the used oligonucleotide probes. For instance, the introduction of the nick into oligonucleotide containing the target base (uracil) resulted in the substantial decrease of uracil DNA glycosylase activity of both the bacterial glycosylase and glycosylases naturally present in nuclear lysates.
Keywords: DNA Repair; lidé; oligonukleotidové sondy; Cell Nucleus; buněčné jádro; magnetické nanočástice oxidů železa; Oligonucleotide Probes; Humans; Uracil-DNA Glycosidase; surface plasmon resonance; uracil-DNA-glykosidasa; base excision repair; oprava DNA; Fluorescence Resonance Energy Transfer; Magnetic Iron Oxide Nanoparticles; uracil DNA glycosylase; rezonanční přenos fluorescenční energie; Förster resonance energy transfer; immobilized oligonucleotides